Application of computational thermodynamics to Fe/Ni, Fe-3%Si/Ni and 316L/Ni systems produced by powder metallurgy. (8th August 2017) - Neves, G. O.; Tirollo, H. G.; Probst, S. M. H.; Binder, C.; Klein, A. N.
ABSTRACT: The commercial simulation software packages, Thermo-Calc and DICTRA, are widely used to predict phase formation and diffusion in materials prepared by traditional metallurgical processes. The goal of this work was to clarify whether the software can also be applied to materials produced by powder metallurgy techniques. For this purpose, diffusion couples of the material combinations Fe/Ni, Fe-3%Si/Ni and 316L/Ni were prepared by two techniques: co-pressing of powders followed by co-sintering and joining of two sintered parts followed by annealing. Thermo-Calc and DICTRA were used to predict interface formation and phase transformations during heat treatments. Scanning electron micrography and energy-dispersive X-ray spectrometry showed the formation of interdiffusion interfaces. The diffusion rate was higher in co-sintered couples, resulting in broader interdiffusion zones than those predicted by simulations, but the annealed couples exhibited interdiffusion profiles similar to those predicted by DICTRA simulations. In general, simulations and experimental results showed the same tendencies.